2020
DOI: 10.1074/jbc.ra119.012023
|View full text |Cite
|
Sign up to set email alerts
|

The tethering function of mitofusin2 controls osteoclast differentiation by modulating the Ca2+–NFATc1 axis

Abstract: Dynamic regulation of the mitochondrial network by mitofusins (MFNs) modulates energy production, cell survival, and many intracellular signaling events, including calcium handling. However, the relative importance of specific mitochondrial functions and their dependence on MFNs vary greatly among cell types. Osteoclasts have many mitochondria, and increased mitochondrial biogenesis and oxidative phosphorylation enhance bone resorption, but little is known about the mitochondrial network or MFNs in osteoclasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…We next examined whether Sirt3 deletion altered the abundance of proteins involved in mitochondria dynamics and mitophagy. Mitofusin2 mediates the tethering of adjacent mitochondria, as well as the tethering of mitochondria to the endoplasmic reticulum (ER), and promotes osteoclast differentiation ( 35 ). Sirt3 deletion had no impact on the protein levels of Mitofusin2 in BMM stimulated with RANKL ( Figure 6E ).…”
Section: Resultsmentioning
confidence: 99%
“…We next examined whether Sirt3 deletion altered the abundance of proteins involved in mitochondria dynamics and mitophagy. Mitofusin2 mediates the tethering of adjacent mitochondria, as well as the tethering of mitochondria to the endoplasmic reticulum (ER), and promotes osteoclast differentiation ( 35 ). Sirt3 deletion had no impact on the protein levels of Mitofusin2 in BMM stimulated with RANKL ( Figure 6E ).…”
Section: Resultsmentioning
confidence: 99%
“…The role of Mfns in osteoclasts has been previously reported [24,25]. Dual deletion of Mfn1 and Mfn2 in the osteoclast lineage leads to increased bone mass in female mice in vivo [25].…”
Section: Discussionmentioning
confidence: 99%
“…Dual deletion of Mfn1 and Mfn2 in the osteoclast lineage leads to increased bone mass in female mice in vivo [25]. Loss of Mfn2 also leads to increased bone mass in vivo [25]. Mechanically, Mfn2 mediates connections between endoplasmic reticulum and mitochondria, which generates large fluctuations in cytoplasmic Ca 2+ that drives NFATc1 activation [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these observations, osteoclasts are multinucleated giant cells that contain a very high density of mitochondria, and increased mitochondria biogenesis and oxidative phosphorylation increase bone resorption. Interestingly enough, very recent studies revealed that mitofusin 2 facilitates osteoclastogenesis by modulating calcium -calcineurin -NFATc1 (Nuclear factor of activated T-cell cytoplasm1); thus, it is tempting to propose that mitochondria function might be damaged in CTNS deficient osteoclasts [37,38]. The study of proximal tubular kidney cells obtained from healthy donors and patients with cystinosis reveals that cystinosin deficiency is associated with altered mammalian target of rapamycin complex 1 (mTORC1) signaling, characterized by abnormal lysosomal retention of mTORC1 during starvation followed by delayed reactivation of mTORC1 [39].…”
Section: Bone Disease and Nephropathic Cystinosis: A Functional Impairment Of Both Osteoblasts And Osteoclastsmentioning
confidence: 99%